Functional heterogeneity of L3T4+ T cells in MRL-lpr/lpr mice. L3T4+ T cells suppress major histocompatibility complex-self-restricted L3T4+ T helper cell function in association with autoimmunity (The Rockefeller University Press, 1988)
The present study demonstrates in MRl-lpr/lpr autoimmune mice an age- dependent loss of MHC-self-restricted function by L3T4+ Th. This defect is not present in age-matched, congenic MRL-+/+ spleen cells and appears to be due to the presence of suppressor cells that are selective for L3T4+ Th and not for Lyt-2+ Th. Surprisingly, the suppressor cells are also L3T4+ T cells and can suppress the IL-2 production of congenic MRL/+ L3T4+ Th to MHC-self-restricted antigens. These data support the idea of functional specialization within the L3T4+ population of T cells. Because L3T4+ suppressor cells are detected late in the course of autoimmunity, we interpret their presence not as a primary initiating event in the development of autoimmunity, but rather as a compensatory mechanism. Additionally, similar suppression of L3T4+ Th function has also been reported in a murine graft-vs.-host model of autoimmunity, suggesting that the suppressor cells represent an immunoregulatory mechanism that is a common feature of autoimmunity. Since excessive class II-restricted Th activity for B cells has been reported for both models of autoimmunity, L3T4+ suppressor cells may represent an attempt to down regulate such excessive Th activity. These findings may be relevant to human autoimmune diseases, such as systemic lupus erythematosus, in which B cell hyperactivity is also associated with reduced IL-2 production by Th.